The Isolation and Characterization of Phenolic Compound of Euphorbia Plant/Patikan Cina (Euphorbia thymifolia Linn) - Amanda, Hilda (Talenta Publisher, 2019)
Euphorbia plant, Euphorbia thymifolia Linn, is one the Euphorbiaceae families that still need to be developed due to its benefits. An effort to be able to use this plant maximumly is by studying the active component in the plant. This study aims to isolate and characterize phenolic compound in euphorbia plant extract using ethyl acetate. 500 gram of euphorbia plant (Patikan Cina) powder was macerated using methanol. Then, the macerated extract was evaporated to eliminate excess solvent and as a result, a solvent-free extract was obtained. Next, the result was partitioned with a solution of methanol : ethyl acetate (1:1) in order to get methanol and ethyl acetate extracts. The ethyl acetate extract of the partition was evaporated to get concentrated ethyl acetate extract. Next, it was isolated in a vacuum liquid and gravitational column chromatography to get pure isolate. Silica gel 60 (0.040 â€“ 0.063 mm) and n-hexane motion phase were used in the separation of concentrated ethyl acetate in vacuum liquid chromatography. There were 16 fractions produced from the yield. Then the fractions were put in TLC. With silica gel 60 (0.2 â€“ 0.5 mm) mesh and n-hexane mobile phase, ethyl acetate gave 5 fractions in gravitational column chromatography and fraction 3 produced a single spot. UV and IR spectroscopy were used to determine the constituents in the isolate. From UV spectrum, ï¬max is 268.97 nm. While IR data shows the presence O-H group in 3521.38 cm-1, C â€“ H (alkane) presents at wave number 2926.45 cm-1 reinforced by the appearance of 5 other alkanes absorption at 2857.00 cm-1, 1447.31 cm-1, 1370.18 cm-1, 868.774 cm-1 and 757.887 cm-1 wavelengths. There is also C = O (carbonyl) groups in wave number 1693.19 cm-1. The identification of structures based on UV and IR spectra data has shown that the isolate is a phenolic compound.